Protocol for the atWork trial: a randomised controlled trial of a workplace intervention targeting subjective health complaints - Tone Langjordet Johnsen; Aage Indahl; Valborg Baste; Hege Randi Eriksen; Torill Helene Tveito (BMC, 2016)
Abstract Background Subjective health complaints, such as musculoskeletal and mental health complaints, have a high prevalence in the general population, and account for a large proportion of sick leave in Norway. It may be difficult to prevent the occurrence of subjective health complaints, but it may be possible to influence employees' perception and management of these complaints, which in turn may have impact on sick leave and return to work after sick leave. Long term sick leave has many negative health and social consequences, and it is important to gain knowledge about effective interventions to prevent and reduce long term sick leave. Methods/Design This study is a cluster randomised controlled trial to evaluate the effect of the modified atWork intervention, targeting non-specific musculoskeletal complaints and mental health complaints. This intervention will be compared to the original atWork intervention targeting only non-specific musculoskeletal complaints. Kindergartens in Norway are invited to participate in the study and will be randomly assigned to one of the two interventions. Estimated sample size is 100 kindergartens, with a total of approximately 1100 employees. Primary outcome is sick leave at unit level, measured using register data from the Norwegian Labour and Welfare Administration. One kindergarten equals one unit, regardless of number of employees. Secondary outcomes will be measured at the individual level and include coping, health, job satisfaction, social support, and workplace inclusion, collected through questionnaires distributed at baseline and at 12 months follow up. All employees in the included kindergartens are eligible for participating in the survey. Discussion The effect evaluation of the modified atWork intervention is a large and comprehensive project, providing evidence-based information on prevention of long-term sick leave, which may be of considerable benefit both from a societal, organisational, and individual perspective. Trial registration Clinicaltrials.gov: NCT02396797 . Registered March 23th, 2015.